Making Porosity More Porous - Juan Esteban de Jager (Svetovi, 2024)
This article explores the potential of “porosity” in understanding the “supernatural”, particularly in interactions with spirits and gods. According to Luhrmann, a “porous” self is key to experiencing the supernatural. Unlike a “buffered” self with a compacted boundary between mind and world, a porous self integrates anomalous experiences more easily. Sharing Luhrmann’s transdisciplinary approach, this article looks into the potential of porosity in addressing reflexivity challenges and phenomenological ones, while advocating for more porous transdisciplinary communication.